Metal organic chemical vapour deposition regrown large area GaN‐on‐GaN current aperture vertical electron transistors with high current capability. Issue 3 (7th January 2021) - Doering, Philipp; Driad, Rachid; Reiner, Richard; Waltereit, Patrick; Mikulla, Michael; Ambacher, Oliver
Abstract: In this work, a large area current aperture vertical electron transistor (CAVET) is fabricated on bulk GaN substrates grown by metal organic chemical vapour deposition (MOCVD). The current blocking layer (CBL) is formed by low dose Mg‐implantation to allow for MOCVD regrowth under standard growth conditions, which simultaneously serves as an in‐situ annealing process. Small transistors are evaluated regarding gate‐aperture overlap ( L GAP ) to derive a robust layout in order to suppress source‐drain leakage. Optimized gate‐aperture dimensions are adopted and combined with a common comb structure design and the established gate‐source module of the lateral HEMT to demonstrate a large area CAVET comb structure. The multi‐finger device exhibits an on‐state resistance of R ON = 2.15 Ω and a chip area of A = 2 × 2 mm². The large area CAVET reveals a maximum drain current of I D, MAX = 20.1 A at a drain‐source voltage of V DS = 45 V, corresponding to a power of P = 900 W.